Kidney complications associated with COVID-19 infection and vaccination in children and adolescents: a brief review - Hee Sun Baek; Min Hyun Cho (The Korean Pediatric Society, 2023)
Coronavirus disease 2019 (COVID-19) has spread considerably across the globe, affecting numerous children and adolescents besides adults. Despite its relatively lower incidence rates in children and adolescents than in adults, some infected children and adolescents exhibit a severe postinflammatory response known as multisystem inflammatory syndrome in children, followed by acute kidney injury, a common complication. Meanwhile, few reports have been available regarding kidney complications such as idiopathic nephrotic syndrome and other glomerulopathies associated with COVID-19 infection and vaccination in children and adolescents. However, the morbidity and mortality of these complications are not exceptionally high; more importantly, causality has yet to be clearly established. Finally, vaccine hesitancy in these age groups should be addressed, considering the strong evidence of COVID-19 vaccine safety and efficacy.